ANALISIS KEMAMPUAN PEMECAHAN MASALAH MATEMATIS SISWA SMP DILIHAT DARI TINGKAT SELF CONFIDENCE TINGGI DALAM MENYELESAIKAN SOAL SPLDV BERBASIS KEMARITIMAN - Marisah, Marisah; Asma Riani Siregar, Nur; Hilda Syani Putri, Nurul (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Mathematical problem-solving skills are an essential competency for students, yet in Indonesia, this competency remains relatively low, according to the 2022 PISA results. A similar situation was observed at SMP Negeri 3 Bintan, where students still struggle to model problems mathematically in the SPLDV curriculum a challenge believed to be linked to low self-confidence. This study aims to describe the mathematical problem-solving skills of students with high self-confidence in solving maritime themed SPLDV problems. This study employs a descriptive method with a qualitative approach, focusing on two eighth-grade students from Class VIII.A at SMP Negeri 3 Bintan, selected through purposive sampling. Data were collected using a self-confidence questionnaire, a mathematical problem-solving ability test, and interviews; they were then analyzed through data reduction, data presentation, and drawing conclusions. The results of the study indicate that students with high self-confidence are able to understand problems and plan solutions well and successfully, but they are not yet optimal in the stages of solving problems according to plan and performing a final check. Therefore, high self-confidence does not guarantee that students are able to complete all stages of mathematical problem solving.